IMPLEMENTASI BUDAYA ORGANISASI DALAM PENINGKATAN PELAYANAN ADMINISTRASI PENDIDIKAN DI MAN I MAKASSAR - Agussalim, M. Ahsan; Siraj, Arifuddin; Ahmad, La Ode Ismail (Idaarah: Jurnal Manajemen Pendidikan, 2018)
Abstract: This study aims (1) To find out the organizational culture implemented in MAN I Makassar (2) the administrative service system in MAN 1 Makassar (3) The impact of implementing organizational culture in improving administrative services in MAN 1 Makassar. This study uses qualitative methods and phenomenological, pedagogical, sociological and psychological approaches. To obtain data, the author have interviews, observation, documentation and triangulation. The results of this study indicate that the implementation 1 Makassar has been well implemented which takes the form of the of organizational culture in improving administration services at MAN application of a culture of discipline and cooperation that refers to the values of social relations and good communication among personal peers who have been determined to achieve aim. Efforts to improve administrative services observed at MAN 1 Makassar have demonstrated their quality, one of which is to prove harmoniously a relationship between fellow personalities, from students, employees, teachers, and principals, which can be realized in the form of cooperation, both in nature structural and cultural. The implication of this research is that it is expected that the school of Madrasah Aliyah Negeri 1 Makasssar can improve its administrative services while still referring to human values and also can be applied effectively and efficiently.